Progress and Prospect of Organic Electrocatalysts in Lithium−Sulfur Batteries - Dong, Yangyang; Li, Tingting; Cai, Dong; Yang, Shuo; Zhou, Xuemei; Nie, Huagui; Yang, Zhi (Frontiers in Chemistry, 2021)
Lithium−sulfur (Li−S) batteries featured by ultra-high energy density and cost-efficiency are considered the most promising candidate for the next-generation energy storage system. However, their pragmatic applications confront several non-negligible drawbacks that mainly originate from the reaction and transformation of sulfur intermediates. Grasping and catalyzing these sulfur species motivated the research topics in this field. In this regard, carbon dopants with metal/metal-free atoms together with transition–metal complex, as traditional lithium polysulfide (LiPS) propellers, exhibited significant electrochemical performance promotions. Nevertheless, only the surface atoms of these host-accelerators can possibly be used as active sites. In sharp contrast, organic materials with a tunable structure and composition can be dispersed as individual molecules on the surface of substrates that may be more efficient electrocatalysts. The well-defined molecular structures also contribute to elucidate the involved surface-binding mechanisms. Inspired by these perceptions, organic electrocatalysts have achieved a great progress in recent decades. This review focuses on the organic electrocatalysts used in each part of Li−S batteries and discusses the structure–activity relationship between the introduced organic molecules and LiPSs. Ultimately, the future developments and prospects of organic electrocatalysts in Li−S batteries are also discussed.